Jurassic World - Trevorrow, Colin, 1976-; Marshall, Frank; Crowley, Patrick Timothy; Jaffa, Rick; Silver, Amanda; Connolly, Derek; Pratt, Chris, 1979-; Howard, Bryce Dallas, 1981-; Simpkins, Ty; Khan, Irrfan, 1962-; D'Onofrio, Vincent; Robinson, Nick, 1995-; et al.
Twenty-two years following the events of Jurassic Park, Isla Nublar now includes a completely functioning dinosaur theme park, as once envisioned by John Hammond. After ten years of operation and decline in visitors, a unique attraction is designed to ignite visitor's interest, which fails horribly.
Based on characters created by Michael Crichton.
Originally produced as a motion picture in 2015.
Widescreen.
Bonus features include deleted scenes ; Chris & Colin take on the World ; dinosaurs roam once again.
Chris Pratt, Bryce Dallas Howard, Ty Simpkins, Irrfan Khan, Vincent D'Onofrio, Nick Robinson, Jake Johnson, Omar Sy, Judy Greer, BD Wong.
DVD ; NTSC, region 1, anamorphic widescreen (2.00:1) presentation ; Dolby digital 5.1 surround (English, Spanish and French) and 2.0 stereo. surround (English DVS).
Keywords: Amusement parks; Dinosaurs; Paleontology -- Jurassic; Jurassic Geologic Period; Feature films -- United States; Action and adventure films; Science fiction films; Thrillers (Motion pictures); Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Action; Drama